A Theory of Dynamic Inflation Targets - Clayton, Christopher; Schaab, Andreas (American Economic Review, 2025)
Should central banks’ inflation targets remain set in stone? We study a dynamic mechanism design problem between a government and a central bank. The central bank has persistent private information about structural shocks. Firms learn the state from the central bank’s reports and form inflation expectations. A dynamic inflation target implements the full-information commitment allocation. The central bank is delegated the authority to adjust the target’s level and flexibility one period in advance. A declining natural interest rate and a flattening Phillips curve imply opposite optimal target adjustments. Our results speak to practical policy questions of inflation target design. (JEL D82, E12, E31, E52, E58)